Multilingual Online Academic Collaborations As Resistance : Crossing Impassable Borders - Giovanna Fassetta; Nazmi Al-Masri; Alison Phipps (Multilingual Matters, 2020)
This book details online academic collaborations between universities in Europe, the USA and Palestine. The chapters recount the challenges and successes of online collaborations which promote academic connections and conversations with the Gaza Strip, despite a continuing blockade imposed on Gaza since 2007, and forge relationships between individuals, institutions and cultures. The chapters examine, from different perspectives, what happens when languages and the internet facilitate encounters, and the fundamental importance this has as a form of defiance and of resistance to the physical confinement experienced by Palestinian academics, students and the general population of Gaza. They highlight the limitations of multilingual and intercultural encounters when they are deprived of the sensory proximity of face-to-face situations and what is lost in the translation of languages, practices and experiences from the ‘real'to the ‘virtual'world. This book is open access under a CC BY NC ND licence.